2013
DOI: 10.7567/apex.6.013001
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Behavior of Uniaxial Anisotropy along [100] Direction in GaMnAs Films

Abstract: We have investigated a uniaxial anisotropy along the [100] direction of GaMnAs film grown on (001) GaAs. The hysteresis observed in the angular dependence of the planar Hall resistance shifted toward the [010] and [010] directions. This phenomenon was analyzed by introducing an additional uniaxial anisotropy field Hu2 along the [100] direction. The magnitude of Hu2 is much smaller than those of the cubic Hc and uniaxial Hu1 anisotropy fields for this material. The temperature behavior of Hu2 appears to be very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…6(a) . This type of hysteresis shift in opposite direction across the two positions (i.e., at and ) was also observed in GaMnAs film having a weak uniaxial anisotropy along the direction 31 32 .…”
Section: Resultssupporting
confidence: 66%
“…6(a) . This type of hysteresis shift in opposite direction across the two positions (i.e., at and ) was also observed in GaMnAs film having a weak uniaxial anisotropy along the direction 31 32 .…”
Section: Resultssupporting
confidence: 66%
“…[23,24]. We are not able to provide definite reason for the observation of 90 different additional uniaxial anisotropy at current stage because it is discovered quite recently as mentioned earlier and its detail investigation has not been done yet.…”
Section: Resultsmentioning
confidence: 53%
“…4. This asymmetric shift of hysteresis is known to be caused by the influence of another type of uniaxial anisotropy along the <100> directions [23,24]. The direction of hysteresis shift in the sample annealed at 300 C for 3 h corresponds to the presence of additional uniaxial anisotropy along the [100] (and the ½100) while the shift to the opposite direction in all other samples including as-grown sample corresponds to presence of uniaxial anisotropy along the [010] (and the ½010) direction.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous experimental studies have revealed the complex nature of the magnetic anisotropies of a GaMnAs film within the film plane. For example, cubic anisotropy in the <100> directions, uniaxial anisotropy in the <110> directions, and another uniaxial anisotropy in the [100] direction have been detected in a GaMnAs film [10][11][12][13][14][15][16]. These anisotropies show dependence not only on the material parameters, as previously mentioned, but also on the temperature [17,18].…”
Section: Introductionmentioning
confidence: 58%